2006
DOI: 10.1016/j.nucmedbio.2006.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing pancreatic β-cell mass with [11C]DTBZ

Abstract: Abstractβ-Cell mass (BCM) influences the total amount of insulin secreted, varies by individual and by the degree of insulin resistance, and is affected by physiologic and pathologic conditions. The islets of Langerhans, however, appear to have a reserve capacity of insulin secretion and, overall, assessments of insulin and blood glucose levels remain poor measures of BCM, β-cell function and progression of diabetes. Thus, novel noninvasive determinations of BCM are needed to provide a quantitative endpoint fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 57 publications
7
98
1
1
Order By: Relevance
“…Using multimodal imaging and inducible and selective beta-cell ablation, we demonstrate that the PET signal from radiolabeled VMAT2 ligands in the mouse pancreas does not correlate with beta-cell mass. Despite the loss of beta cells after DT administration, as monitored by BLI, mice with reduced beta-cell mass did not exhibit lower pancreatic retention of three different (24), may account for the reduced binding of [ 11 C]DTBZ after streptozotocin that was noted in previous reports (21,25).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Using multimodal imaging and inducible and selective beta-cell ablation, we demonstrate that the PET signal from radiolabeled VMAT2 ligands in the mouse pancreas does not correlate with beta-cell mass. Despite the loss of beta cells after DT administration, as monitored by BLI, mice with reduced beta-cell mass did not exhibit lower pancreatic retention of three different (24), may account for the reduced binding of [ 11 C]DTBZ after streptozotocin that was noted in previous reports (21,25).…”
Section: Discussionmentioning
confidence: 62%
“…Previous studies investigating radiolabeled DTBZ analogs for imaging the beta cell have led to contradictory conclusions. Studies in rodent models (21,22,25) and humans (23) have demonstrated a decrease in radiotracer retention in the pancreas of diabetics. However, other groups have found high radiotracer binding to the exocrine pancreas of rodents and humans (24,33,34) with reduced exocrine binding in the diabetic pancreas (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DTBZ can also be used to monitor BCM quantitatively for diabetes. PET tracers that have been used to quantify VMAT2 are [ 11 C]-dihydrotetrabenazine ([ 11 C]-DTBZ) ; Simpson et al, 2006;Murthy et al, 2008;Goland et al, 2009) (Kung et al, 2008(b)), which were shown to have high potency and selectivity for binding to VMAT2 in rats.…”
Section: Measurement Of Pancreatic -Cell Mass In the Development Of mentioning
confidence: 99%
“…PET studies of VMAT2 pathophysiology are in their infancy; however, several important studies have been published by the group at Columbia University (19)(20)(21). In an investigation (19) with 11 C-DTBZ, they demonstrated decreased radioligand uptake in the pancreas of Lewis rats with streptozotocin-induced diabetes, compared with euglycemic historical controls.…”
mentioning
confidence: 99%